The Demand for Pediatric Care: An Hedonic Approach - Goldman, Fred; Grossman, Michael (Journal of Political Economy, 1978)
When the quality of a good varies, quantity in physical units may be a very misleading measure of total consumption. In this paper it is argued that differences in quality are a distinguishing feature of the market for physicians' services. We develop a model to analyze properties of demand functions for the quantity and quality of physicians' services and apply the model to study the demand for pediatric care–physicians' services rendered to children. The theoretical model of quantity-quality substitution provides a framework for demand analysis whenever the market for a good is distinguished by a quality component.